Description Preparedness Of Health Workers In Disaster Management In Public Health Center Disaster Vulnerable Area In Lhok Bengkuang Health Center - Yenni Sasmita; Fathimi Fathimi; Hilma Yasni; Desriati Devi; Zakirullah Zakirullah (Information Technology and Science (ITScience), 2025)
Background: This research provides an overview of the role of health workers in disaster preparedness at Community Health Centers and provides information regarding implementation strategies that health workers can use both in preparing for and responding to disasters. Objective: to understand the preparedness of health workers in disaster management at the Lhok Bengkuang Community Health Center, South Aceh Regency. Method: This type of research is quantitative research with a cross sectional approach. The population in this study was 82 health workers in the Lhok Bengkuang Tapaktuan Health Center Working Area in 2023. The sample taken in this study used an accidental sampling technique totaling 70 people. Results: The research results showed that of the 70 respondents, 44 people were less prepared to face disasters, 20 people were ready to face disasters. Of the 70 respondents, 38 people had <10 years of work experience, and 32 people had ?10 years of work experience. There were 32 people who had little knowledge about disasters and 36 had a positive attitude towards disasters. And there were 44 people who stated that disaster preparedness was lacking. Conclusions and Suggestions: There is a significant relationship between education, knowledge, attitudes and work experience and the preparedness of health workers in facing disasters in the Lhok Bengkuang Health Center work area, Tapaktuan. It is hoped that health workers at Community Health Centers can increase awareness and ability to prepare for disasters.